Faktor-faktor yang Berhubungan dengan Higienitas Pasien Skabies di Puskesmas Panti Tahun 2014 (Factors Related to Hygiene of Scabies Patients in Panti Primary Health Care 2014) - Ika Sriwinarti; Wiwien Sugih Utami; Ida Srisurani Wiji Astuti (Pustaka Kesehatan, 2015)
Scabies is one of the health problems in developing countries and developed countries. Scabies is easier to invest in people who have poor personal hygiene. Risk factors that may affect the hygiene of scabies consist of internal and eksternal factors. The purpose of this study was to analyze the factors which affect the hygiene of scabies patients. This study was a quantitative research with cross sectional approach. Sample was obtained by quota sampling from patients who visited Panti primary health care in 2014. The factors studied were age, gender, education, occupation, marital status and residence. Data analysis was performed by chi square test and logistic regression. Chi square test found significant factors related to the hygiene were age (p=0,002), education (p=0.015), occupation (p=0,029), marital status (p=0,029) and residence (p=0.015) while other factors did not significant. Results of logistic regression test for age p=0.019 OR=0.000, education p=0.045 OR=4.327, occupation p=1,000 OR=0,000, marital status p=0,999 OR=0,000 and residence p=1,000 OR=2,989. Based on this study, it can be concluded that education was the most affecting factor correlated to hygiene of scabies patients. Keywords: hygiene, scabies, Panti primary health care